E. E. Constance Jones on Existence in a Region of Supposition - Ben Caplan (Journal for the History of Analytical Philosophy, 2023)
In “On the Nature of Logical Judgment” (published 1893) and A New Law of Thought and Its Logical Bearings (published 1911), E. E. Constance Jones developed a view on which we can think and talk about the round-square. On her view, the round-square has a kind of existence; otherwise, sentences about it wouldn’t be meaningful. But it doesn’t exist in space, since it’s both round and square, and nothing in space is both. Although it has a kind of existence in what she calls “a Region of Supposition,” we can truly say that it “doesn’t exist,” if what we mean is that it doesn’t exist in space. It plays a role in reasoning, since we need to be able to reason about it to conclude that it doesn’t exist in space. And, although the round-square is both round and square, the Law of Contradiction needn’t be violated, provided that it’s understood in light of Jones’s distinction between two kinds of negation.